Biodegradable hyaluronan hydrogel coatings on acellular dermis grafts—A potential strategy to improve biologic graft durability in hernia repair application. Issue 8 (12th March 2019) - Sahoo, Sambit; Ma, Jinjin; Tastaldi, Luciano; Baker, Andrew R.; Loftis, Jacki; Rosen, Michael J.; Derwin, Kathleen A.
Abstract: Biologic grafts used in hernia repair undergo rapid cellular infiltration and remodeling, but their premature degradation often results in hernia recurrence. We hypothesize that a temporary barrier that prevents infiltration of acute inflammatory cells into the graft during the initial 4 weeks of implantation could mitigate graft degradation. The purpose of this study is to design tyramine‐substituted hyaluronan (THA) hydrogel coatings with tunable degradation properties, as a means to develop a resorbable barrier for human acellular dermis grafts (HADM). THA plugs prepared at different cross‐linking densities, by varying cross‐linking agent concentration (0.0001–0.0075% H2 O2 ), demonstrated varying rates of in vitro degradation (25 U/mL hyaluronidase, 48 h). Based on these results, HADM grafts were coated with THA at three cross‐linking densities (0.0001%, 0.00075%, and 0.003% H2 O2 ) and THA coating degradation was evaluated in vitro (25 U/mL hyaluronidase, 48 h) and in vivo (rat intraperitoneal implantation, 1–4 weeks). THA coatings degraded in vitro and in vivo with the lowest cross‐linking density (0.0001% H2 O2 ), generally showing greater degradation as evidenced by significant decrease in coating cross‐sectional area. However, all three coatings remained partially degraded after 4 weeks of in vivo implantation. Alternate strategies to accelerate in vivo degradation of THA coatings are required to allow investigation of the study hypothesis. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B:2664–2672, 2019.